Pomegranate juice powder as sugar replacer enhanced quality and function of set yogurts: Structure, rheological property, antioxidant activity and in vitro bioaccessibility. (November 2019) - Pan, Li-Hua; Liu, Fei; Luo, Shui-Zhong; Luo, Jian-ping
Abstract: Phenolics are good natural antioxidant in human diets and contribute to formation of sensory attributes of food products. This study aimed to investigate effects of 1%–5% pomegranate juice powder (PJP, rich in phenolics) used as sugar in fermentation matrix on the physiochemical properties (color, sensory and total phenolic content), structure (texture and microstructure), rheology and functionality (antioxidant activity and in vitro bioaccessibility) of set yogurts during storage for 21 days. It showed that the higher PJP level, the higher sensory scores and total phenolic contents the yogurt had, the firmer in texture and compacter in microstructure became, and the better viscoelasticy and stronger antioxidant activity exhibited. But there was no significant difference (P > 0.05) in color and bioaccessibility between controls and yogurts with PJP. During the storage, except for the consistency of LD was slightly lower than that of the control on the first day and at the end of storage, the values of other quality attributes of the LD, MD, MD groups showed higher than that of the controls. Results indicated that 5% PJP has potential to improve quality attributes of set yogurt by replacing sucrose in fermentation matrix. Highlights: 1%–5% pomegranate juice powder (PJP) was used as a sugar replacer for set yogurts production. PJP improved gel viscoelasticity, antioxidant activity and storage stability of set yogurts. Enhancement effects on set yogurts increased with the increasing levels of PJP replacement. PJP can replace some or all sucrose in fermentation matrix for the production of functional yogurt.